University-business collaboration perspective in logistics management curriculum design - Novi Indah Susanthi; Mohammad Ali; Asep Herry Hernawan; Ari Indra Susanti (Himpunan Pengembang Kurikulum Indonesia, 2026)
The study explores the integration of industry-relevant competencies into logistics management education, emphasizing the alignment between professional demands and curriculum structure. The purpose of this study is to design a logistics management curriculum grounded in graduate competencies to prepare graduates to work and adapt in the future logistics industry. The study employed a quantitative approach within the Design and Development Research (DDR) phase three. The 3rd phase involved designing the curriculum after analyzing needs (the 1st phase) and selecting the competencies required of logistics management graduates (the 2nd phase). The curriculum was designed using 5 components: competencies, learning objectives, content, learning strategies, and evaluation. The curriculum template was adapted from the “Pedoman Pendidikan Tinggi” in Indonesia and aligned with the institution’s guidance. The results show that two competencies, business logistics and interpersonal skills, both have higher values than logistics management competencies due to the abilities needed to adapt to the world of the future logistics industry, which is always challenging. The study is expected to inform logistics education by emphasizing business logistics and interpersonal skills, while strengthening regulation-based logistics management competencies. Abstrak Studi ini mengeksplorasi integrasi kompetensi yang relevan dengan industri ke dalam pendidikan manajemen logistik, menekankan keselarasan antara tuntutan profesional dan struktur kurikulum. Tujuan penelitian ini adalah untuk merancang kurikulum manajemen logistik berdasarkan kompetensi lulusan yang dibutuhkan agar mampu bekerja dan beradaptasi di masa depan, terutama dalam industri logistik. Studi ini menggunakan metode kuantitatif dengan fase ketiga Penelitian Desain dan Pengembangan (DDR) sebagai pendekatan. Fase ketiga adalah merancang kurikulum setelah menganalisis kebutuhan (fase pertama) dan memilih kompetensi yang dibutuhkan untuk lulusan manajemen logistik (fase kedua). Kurikulum dirancang menggunakan 5 komponen sebagai berikut: kompetensi, tujuan pembelajaran, isi materi, strategi pembelajaran, dan evaluasi. Template kurikulum menggunakan